Smart and security home system / Bakhtiar Hakim Abd Jalal - Abd Jalal, Bakhtiar Hakim (2007)
This project describes the development of Smart and Security Home System. It focuses on the design of hardware and software modules. This system designed to control a system of home appliances. In order to allow this system to function, all devices must be connected to the computer via hardware interface. VB 6.0 software is used as the controller to control the lamps of Smart and Security Controller Box. Therefore, the Personal Computer (PC) will able to interact with hardware for control purposes. This system is accessible to user anywhere, anytime and any day.